Optimization of Slow Pyrolysis of Bamboo for Biochar Production using Taguchi’s L9 Orthogonal Array - Moni MNZ; Yusuf Suzana; Manaf ASA; Rahman Waqiuddin (E3S Web of Conferences, 2021)
This paper investigates the effects of three parameters (reaction temperature, feedstock particle size and nitrogen flow rate) towards the solid (char) yield from the pyrolysis of bamboo. Three-factor, three-level Taguchi’s L9 Orthogonal Array was used as the experimental design. The char yield at reaction temperatures of 300-500°C, feedstock particle size of 100-1000 μm, and nitrogen flow rate of 100-300 ml min−1 were investigated. The maximum solid yield was predicted based on signal-to-noise (S/N) ratio and was found to be at 300°C reaction temperature, 1000 μm feedstock particle size and 100 ml min−1 of nitrogen flow rate. Confirmation runs were conducted to validate the prediction at corresponding predicted conditions.